2017
DOI: 10.3389/fnins.2017.00380
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cognitive Impairment in Multiple Sclerosis—The Road toward an Imaging-based Biomarker

Abstract: Multiple Sclerosis (MS) is a neuro-degenerative and -inflammatory disease leading to physical and cognitive impairment, pathological fatigue and depression, and affecting patients' quality of life and employment status. The combination of inflammation, demyelination, and neurodegeneration leads to the emergence of MS lesions, reduced white and gray matter brain volumes, a reduced conduction velocity and microstructural changes in the so-called Normal Appearing White Matter (NAWM). Currently, there are very lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 65 publications
(84 reference statements)
0
19
0
Order By: Relevance
“…An important question brought by the analysis of MS‐related rsFC changes and their correlation to cognitive scores, is whether electrophysiological rsFC provides an added value to describe MS‐related CI compared to structural markers that are often used (e.g., brain atrophy, cortical lesions, see e.g., Van Schependom & Nagels, 2017). To address this issue, we focused on cognitive scores that were significantly altered in patients with MS, and we first built for each of them a purely structural regression model with two well‐established markers of neurostructural damage as dependent variables, that is, global lesion load and normalized thalamic volume (see e.g., Barkhof, 2002; Tewarie et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important question brought by the analysis of MS‐related rsFC changes and their correlation to cognitive scores, is whether electrophysiological rsFC provides an added value to describe MS‐related CI compared to structural markers that are often used (e.g., brain atrophy, cortical lesions, see e.g., Van Schependom & Nagels, 2017). To address this issue, we focused on cognitive scores that were significantly altered in patients with MS, and we first built for each of them a purely structural regression model with two well‐established markers of neurostructural damage as dependent variables, that is, global lesion load and normalized thalamic volume (see e.g., Barkhof, 2002; Tewarie et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we added as dependent variables all mean network connectivity values (across RSNs and frequency bands, see Figure 2d) exhibiting a significant MS‐related contrast. Given that structural and functional parameters are related (Tewarie et al, 2013; Van Schependom & Nagels, 2017), these rsFC variables were orthogonalized with respect to the structural parameters before being used in the regression. This merely amounts to a reparametrization that emphasizes the independent information brought by rsFC but leaves the R 2 statistic unchanged.…”
Section: Methodsmentioning
confidence: 99%
“…A sensitive biomarker to detect risk of cognitive dysfunction and treatment-related cognition improvement is therefore urgently required. 8 MRI is a powerful non-invasive diagnostic and monitoring tool for MS and has great potential to detect cognitive dysfunction. However, recent studies showed only weak associations between traditional MRI measures, such as white matter lesion (WML) load and whole brain atrophy, and cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…9 The development of advanced MRI techniques may allow early detection of cognitive dysfunction. 8,10 White matter (WM), gray matter (GM) and WML were found to account for cognitive dysfunction but the contributions were inconsistent among different studies. 1 Thalamic atrophy, among the subcortical gray matter structures, is most promising to predict cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is worthy to note that most of our significant results were confirmations of published reports. Among the others, we obtained significant correlations between the overall corpus callosum atrophy and both the executive functions and depression (Benedict, Ramasamy, Munschauer, Weinstock‐Guttman, & Zivadinov, ; Johnson‐Markve, Lee, Loring, & Viner, ; van Schependom & Nagels, ), whereas the right occipital lobe volume was found significantly related to the performances obtained at SDMT (Akbar et al, ).…”
Section: Discussionmentioning
confidence: 78%